2021
DOI: 10.1080/21623945.2021.1886409
|View full text |Cite
|
Sign up to set email alerts
|

The antihypertensive effect of irbesartan in spontaneously hypertensive rats is associated with improvement of the leptin–adiponectin imbalance

Abstract: Objective: This study aimed to investigate whether the antihypertensive effect of irbesartan (IRB) in spontaneously hypertensive rats (SHR) was achieved through improvement of insulin resistance and adjustment of the LPN–APN imbalance.Methods:SHR rats were divided into SHAM, SHR-A and SHR-I group(8 per group). Homologous Wistar–Kyoto (WKY) rats were used as control group (WKY).The SHR-I group received 30 mg/kg/d IRB, the SHR-A group received 2.5 mg/kg AML. After 8 weeks, systolic blood pressure (SBP) was measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Statistics show that nearly 1 billion people worldwide are suffering from hypertension [1]. Recently, several population-based epidemiological surveys conducted in China reported hypertension prevalence ranging from 26.6 to 33.6% [2].…”
Section: Introductionmentioning
confidence: 99%
“…Statistics show that nearly 1 billion people worldwide are suffering from hypertension [1]. Recently, several population-based epidemiological surveys conducted in China reported hypertension prevalence ranging from 26.6 to 33.6% [2].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, this study also found that the total antihypertensive efficiency of the three‐drug combination regimen at different times was 91.24% and 87.10% for morning and night medication groups, respectively, and they all contributed to blood pressure reduction and improvement of vascular endothelial function and circadian rhythm of blood pressure, which are related to the mechanism of action of the three drugs: (1) Irbesartan can relax blood vessels, reduce the burden on the heart, and restore the circadian rhythm of normal blood pressure, thus correcting the “non‐dipper” curve of blood pressure; it can promote the dilatation of precapillary arteries, resistance arteries and veins, reduce anterior and posterior loads on the heart, thus improving ventricular remodeling and avoiding myocardial hypertrophy and vessel wall thickening caused by long‐term hypertension 17 , 18 ; (2) Hydrochlorothiazide can reduce intracellular calcium ion and sodium‐calcium exchange in vascular smooth muscle, decrease intracellular calcium ion and vascular smooth muscle responsiveness to angiotensin and catecholamines, weaken vasoconstriction, and thus reduce blood pressure; its sustained hypotensive effect may be related to the local release of prostaglandins or other vasodilating substances that reduce small artery dilation and total peripheral resistance 19 , 20 ; (3) Levamlodipine can block L‐type calcium channels and inhibit the transfer of calcium ions into the cells, thus exerting a direct diastolic effect on vascular smooth muscle, improving hemodynamics and regulating blood pressure 21 ; Levamlodipine promotes the release of NO and other potent vasodilatory substances, indirectly diastaging vascular smooth muscle and thus improving vascular endothelial function. Long‐term use of hydrochlorothiazide can produce dose‐related side effects such as elevated uric acid levels, abnormal glucose tolerance, hypokalemia, and reduced insulin sensitivity, while the irbesartan and levamlodipine combination can reduce or counteract the RAAS and sympathetic nerves activation caused by long‐term use of hydrochlorothiazide, which increases the antihypertensive effect and reduces adverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…MMPs and TIMPs were found to play an important role in ventricular remodeling by affecting extracellular matrix degradation and regulating matrix metabolism in myocardial tissue. 16 In this study, we found that the levels of VST, LVEDD, LVM, PWT, LVMI, TIMP-1, and TIMP-2 were lower, and those of MMP-2, MMP-3, and MMP-9 were higher in both groups than before drug Moreover, this study also found that the total antihypertensive efficiency of the three-drug combination regimen at different times was 91.24% and 87.10% for morning and night medication groups, respectively, and they all contributed to blood pressure reduction and improvement of vascular endothelial function and circadian rhythm of blood pressure, which are related to the mechanism of action of the three drugs: (1) Irbesartan can relax blood vessels, reduce the bur-den on the heart, and restore the circadian rhythm of normal blood pressure, thus correcting the "non-dipper" curve of blood pressure; it can promote the dilatation of precapillary arteries, resistance arteries and veins, reduce anterior and posterior loads on the heart, thus improving ventricular remodeling and avoiding myocardial hypertrophy and vessel wall thickening caused by long-term hypertension 17,18 ;…”
Section: Discussionmentioning
confidence: 99%